IMPLICATIONS OF COMPOSITION FOR EXPERIMENTAL PARTITIONING OF PLATINUM-GROUP ELEMENTS AND GOLD BETWEEN SULFIDE LIQUID AND BASALT MELT: THE SIGNIFICANCE OF NICKEL CONTENT - Crocket J.H.; Fleet M.E.; Stone W.E. (My University, 1997)
Experimental partitioning of platinum-group elements (PGE) Os, Ir, Ru, Pt, and Pd, and Au between (Fe, Ni)-sulfide liquid and basaltic melt have been carried out at high Ni content with 67 ± 1 mol% NiS and 50 to 400 ppm PGE in the sulfide fraction. The study was designed to evaluate the significance of major element composition, in particular high Ni content, on partitioning of these noble metals. Charges were held at 1250°C for 48 h. Mean partition coefficients D (wt fraction PGE in sulfide/ wt fraction PGE in silicate) obtained were: and pertain to 7 samples for Os, Ir, and Ru, 6 samples for Pt and Pd, and 5 for Au. The average values for Ir, Ru, Pt, and Pd are comparable with D values reported by Fleet et al. (1996) for a series of 5 samples equilibrated under virtually identical experimental conditions but on charges with lower Ni content. A significant correlation of individual D values with PGE in quenched sulfide was observed for Ru, Pt, and Pd, suggesting that variable concentrations of these metals in initial charges contribute to the inter-experiment variation in D. A marked increase in D(Au) to 13.6 × 101^3 was found when the Au content of initial charges was increased from a ppb to a ppm range, a trend comparable to that of Ru, Pt, and Pd. D(PGE) values for ~50 ppm PGE in the sulfide liquid are D(Ru) = 1.45 × 10^3, D(Pt) = 10.5 × 10^3, and D(Pd) = 17.8 × 10^3. The significance of NiS for PGE-Au partitioning was investigated by comparing D values for controlled atmosphere experiments ranging from ~4 to 67 mol% NiS in quenched sulfide. Sulfide liquids with less than ~38 mol% NiS are associated with more variable D values for all PGE-Au than those of higher NiS content, which yield more consistent D values. Ruthenium is an exception and behaves in a reverse manner. There is no strong correlation of the magnitude of D with composition of the sulfide liquid but rather a correlation of the variance in D. It is suggested that the Ni/Fe proportions of the silicate melt strongly affect the behaviour of PGE-Au in silicate melts, probably through a control on speciation and solubility of noble metals.